Case report: Successful treatment of mediastinal unicentric castleman disease using cardiopulmonary bypass - Ran, Wei; Cuilin, Zhu; Hulin, Piao; Kexiang, Liu (Frontiers in Cardiovascular Medicine, 2023)
Unicentric Castleman disease (UCD) is a rare, benign lymphoproliferative disorder. Mediastinal UCD has tumors with no clear boundaries that are highly vascularized. Resection surgery results in bleeding, leading to further challenges. Mixed-type UCD is rare. We report the case of a 38-year-old asymptomatic patient with mixed-type UCD; the tumor measured 7.8 cm in size and had unclear boundaries. The tumor was successfully resected by performing a cardiopulmonary bypass on the beating heart; the patient recovered uneventfully.